Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11199-009-9625-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Young Women’s Interest in Obtaining Cosmetic Surgery

Abstract: This study examined predictors of young women's interest in obtaining cosmetic surgery. The sample investigated was comprised of 101 college undergraduates residing in the northeastern U.S. (M age=19.99, SD=4.79). Participants' weight status (M BMI=24.52, SD=5.69), body dissatisfaction, internalization of media messages, reports of physical appearance teasing, and interest in obtaining cosmetic surgery were assessed. Results indicated that all of the predictors examined were correlated with women's interest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
88
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 34 publications
(30 reference statements)
9
88
2
2
Order By: Relevance
“…Further studies should use self-report measures of mass media influence that are validated. In conclusion, the present study confirmed the importance of body dissatisfaction as a predictor of in the choice to undergo aesthetic surgery [50] and highlighted the influence of media messages regarding physical appearance. One of the main implications of the present study regards the postoperatory phase.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Further studies should use self-report measures of mass media influence that are validated. In conclusion, the present study confirmed the importance of body dissatisfaction as a predictor of in the choice to undergo aesthetic surgery [50] and highlighted the influence of media messages regarding physical appearance. One of the main implications of the present study regards the postoperatory phase.…”
Section: Discussionsupporting
confidence: 81%
“…Other previous studies have found a link between body dissatisfaction, exposure to media and cosmetic surgery [23] [50]- [52]. Markey and Markey [50] demonstrated that women's body dissatisfaction significantly predicts their interest in cosmetic surgery; moreover, they found that women who were more influenced by the media about physical appearance were also more likely to desire cosmetic surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Considering the age difference (from 14.29 to 19.9), and the lower BMI value reported, we consider the prevalence of normal weight and underweight in our sample confirmed. The BMI comparison is rooted in the European geographical and ethnic space, because a study on young women (M=19.99, SD=4.79) in the USA returns significantly higher values -M=24.52 kg/m2, (SD=5.69), with approximately 30% of the sample maintaining a BMI of 25 or greater, indicating that they were overweight or obese (Markey, Markey, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that those who are more invested in their physical appearance , who internalize media messages about appearance (Markey & Markey, 2009;Swami, 2009), who are more conforming , who are more sensitive to rejection (Park et al, 2009), and who are more materialistic (Henderson-King & Brooks, 2009) are all more likely to express positive attitudes toward cosmetic surgery.…”
Section: Introductionmentioning
confidence: 99%